Rethinking security in the age of migration trust and emancipation in europe - Bilgiç, Ali. (Milton Park, Abingdon, Oxon : Routledge, 2013)
'Migration and especially irregular migration are politically sensitive and highly debated issues in the developed world, particularly in Europe. This book analyses irregular protection-seeking migration in Europe, with close attention to sub-Saharan migration into the EU, and emancipatory security theory'--
pt. 1. Being -- pt. 2. Knowing -- pt. 3. Doing.
Includes bibliographical references (p. [195]-207) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Human rights -- Europe; National security -- Europe; Africa, Sub-Saharan -- Emigration and immigration; Europe -- Emigration and immigration; Electronic books